2017
DOI: 10.5406/amerjpsyc.130.4.0455
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tropical Climate on Mental Rotation: The Role of Imagery Ability

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 57 publications
1
4
0
4
Order By: Relevance
“…This result confirmed those recently obtained by Robin et al (2017) during which participants fulfilled the Movement Imagery Questionnaire Revised (Hall & Martin, 1997) and the a mental rotation test and that showed that TC negatively influenced mental rotation, motor imagery and imagery ability. Similar results were observed during heat exposure in studies using different complex tasks (Hocking et al, 2001;Robin & Coudevylle, 2018;Robin et al, 2019).…”
Section: Climate and Mental Imagerysupporting
confidence: 91%
“…This result confirmed those recently obtained by Robin et al (2017) during which participants fulfilled the Movement Imagery Questionnaire Revised (Hall & Martin, 1997) and the a mental rotation test and that showed that TC negatively influenced mental rotation, motor imagery and imagery ability. Similar results were observed during heat exposure in studies using different complex tasks (Hocking et al, 2001;Robin & Coudevylle, 2018;Robin et al, 2019).…”
Section: Climate and Mental Imagerysupporting
confidence: 91%
“…Depending on their complexity, cognitive tasks may be differently impacted by TC (Robin et al, in press). Whereas heat stress does not affect tasks like simple tasks, more complex tasks such as a pointing task (Ernwein and Keller, 1998;Robin et al, 2017) or sustained attention (Vasmatzidis et al, 2002;Coudevylle et al, 2018) and working memory (Gaoua et al, 2018) tasks are negatively affected. The effects of heat or TC on cognitive performance depend on multiple personal factors − such as level of expertise, sex, hydration status, and heat acclimation − and many external factors, including task duration, the methodology utilized to attain hyperthermia, and the intensity and duration of the thermal stressor (for a review, see Gaoua, 2010;Schmit et al, 2017).…”
Section: Consequences Of Tc For Cognitive Performancementioning
confidence: 99%
“…En effet, [86] ont montré l'utilisation de davantage de ressources cognitives en condition de TE, pour rester concentré, dans des tâches d'attention. Il a ainsi été envisagé que la réduction de la contrainte thermique augmenterait la disponibilité des ressources attentionnelles qui pourraient ensuite être utilisées pour faire face aux demandes cognitives liées à l'exercice et imposées par le stress thermique [4,87]. De même, alors qu'une TE induit généralement une augmentation de la température cutanée qui peut causer de l'inconfort, du déplaisir et détériorer l'activité corticale [24], la limitation de la hausse de cette température au moyen de gilet réfrigéré, de poches de glace ou de serviettes froides pourrait permettre le refroidissement de la peau et ainsi favoriser les performances des athlètes dans des tâches exigeantes sur le plan cognitif [14], lorsque la réglementation le permet.…”
Section: Stratégies De Refroidissement Physiqueunclassified